Influence of hydrothermal pretreatment on acidity and activity of H-GaAlMFI zeolite for the propane aromatization reaction - Choudhary, Tushar V.; Kinage, A.; Banerjee, S.; Choudhary, Vasant R. (Microporous and Mesoporous Materials, 2005)
The acidity and propane aromatization activity of H-GaAlMFI has been investigated subsequent to different hydrothermal (HT) pretreatments. Extensive degalliation of framework Ga occurred during the HT pretreatments; the framework Si/Ga ratio nearly doubled when the steam concentration was increased from 0% to 80%. The extent of degalliation and corresponding loss of strong zeolitic acidity (measured in terms of pyridine chemisorbed at 400 degrees C) was particularly severe at high (> 500 degrees C) temperatures and steam concentrations (> 40 mol%). Framework Al in the GaAlMFI zeolite was found to be very stable; the FW Si/Al ratio did not change to any appreciable extent even after severe HT pretreatments. Each of the HT pretreatment parameters (concentration of steam: 0-80%, HT temperature: 400-600 degrees C and length of HT pretreatment: 0-6 h) showed a profound influence on the propane aromatization activity. The product selectivity was, however, only mildly affected by the HT pretreatments. The following factors were found to be important for high propane aromatization activity (a) strong zeolitic acidity and (b) optimal content/dispersion of the extra-framework Ga species which are formed in situ during the HT pretreatments. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: Acidity; aromatic distribution; Ga-based zeolites; hydrothermal treatment and steam; propane aromatization

Influence of PdO content and pathway of its formation on methane combustion activity - Choudhary, Tushar V.; Banerjee, S.; Choudhary, Vasant R. (Catalysis Communications, 2005)
The methane oxidation reaction is known to induce changes in the surface structure and composition of Pd catalysts; making it extremely arduous to relate the methane oxidation activity to specific catalyst properties by conventional methods (continuous flow reactor studies). To circumvent this, methodical pulse reactor studies have been undertaken to obtain correlations between the initial methane combustion activity and the catalyst properties (Pd-0/PdO content and path of PdO formation). While the initial methane combustion activity (at 160-280 degreesC) continuously increased with increasing PdO concentration (0-100%) in the catalyst, it continuously decreased with increasing Pddegrees content (0-100%). Controlled studies were undertaken to obtain catalysts with identical PdO content by two pathways: (i) by controlled partial oxidization of Pd-0/Al2O3 and (ii) by controlled partial reduction of PdO/Al2O3. Interestingly, for a given PdO content, the catalysts obtained by partial oxidation of Pd-0/Al2O3 showed a significantly superior performance to the catalyst obtained by partial reduction of PdO/Al2O3 for all the temperatures investigated. These studies unambiguously show that along with the relative concentration of PdO, the PdO formation pathway is also critical in deciding the methane combustion activity of the catalyst. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Methane combustion; Oxidation; partially oxidized Pd-0/Al2O3; partially reduced PdO/Al2O3; Pd-0/Al2O3; PdO/Al2O3; pulse reaction of methane

In-Mg-hydrotalcite anionic clay as catalyst or catalyst precursor for friedel-crafts type benzylation reactions - Choudhary, Vasant R.; Jha, Rani; Narkhede, V. S. (Journal of Molecular Catalysis A-Chemical, 2005)
In-Mg-hydrotalcite (Mg/In = 3) anionic clay with or without calcination (at 200-800 degrees C) or HCl pretreatment at different temperatures (26 and 80 degrees C) and periods (0.1 or 1.0 h) has been used for the benzylation of benzene and/or substituted benzenes by benzyl chloride. The hydrotalcite before and after its calcination or HCl pretreatment was characterized for its surface area, crystalline phases and basicity. The hydrotalcite particularly after its use in the benzylation reaction, and the catalyst derived from it by its calcination at 800 degrees C followed by HCl pretreatment (at 80 degrees C for 1.0 h), shows high catalytic activity even for the benzylation of benzene. The catalytically active species present in the catalyst in its most active form are the chlorides and oxides of indium on the catalyst surface. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: activation of In-Mg-hydrotalcite by calcination; activation of In-Mg-hydrotalcite by HCl pretreatment; benzylation of benzene; benzylation of substituted benzenes; In-Mg-hydrotalcite

In situ generation of hydrogen peroxide from reaction of O-2 with hydroxylamine from hydroxylammonium salt in neutral aqueous or non-aqueous medium using reusable Pd/Al2O3 catalyst - Choudhary, Vasant R.; Jana, Prabhas (Catalysis Communications, 2007)
In situ generation of H2O2 with high yield can be accomplished by reacting 02 with NH2OH from hydroxylammonium salt [NH2OH.HCl or (NH2OH)(2) . H2SO4] in a neutral aqueous medium using a reusable heterogeneous Pd (1.0 wt%)/Al2O3 catalyst, even at low temperature (10 degrees C), with the formation of harmless by-products (viz. N-2 and water). The presence of KCl or KBr in the medium has beneficial effect. The H2O2 generation is strongly influenced by the pH of medium, reaction period and temperature; best results are obtained at the optimum pH and reaction medium. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Hydrogen peroxide; hydroxylamine; Hydroxylammonium salt; in situ H2O2 generation; oxygen; Pd/AlO3 catalyst

Influence of alkali metal doping on surface properties and catalytic activity/selectivity of CaO catalysts in oxidative coupling of methane - Rane, V. H.; Chaudhari, Sopan T.; Choudhary, Vasant R. (Journal of Natural Gas Chemistry, 2008)
Surface properties viz. surface area, basicity/base strength distribution, and crystal phases) of alkali metal doped CaO (alkali metal/Ca = 0.1 and 0.4) catalysts and their catalytic activity/selectivity ill oxidative coupling of methane (OCM) to higher hydrocarbons at different reaction conditions (viz. temperature. 700 and 750 degrees C: CH(4)/O(2) ratio. 4.0 and 8.0 and space velocity. 5140-20550 cm(3). g(-1).h(-1)) have been investigated. The influence of catalyst calcination temperature on the activity/selectivity has also been investigated. The surface properties (viz. surface area, basicity/base strength distribution) and catalytic activity/selectivity of the alkali metal doped CaO Catalysts are strongly influenced by the alkali metal promoter and its concentration in the alkali metal doped CaO catalysts. An addition of alkali Metal promoter to CaO results in a large decrease in the surface area but a large increase in the surface basicity (strong basic sites) and the C(2+) Selectivity and yield of the catalysts in the OCM process. The activity and selectivity are strongly influenced by the catalyst calcination temperature. No direct relationship between surface basicity and catalytic activity/selectivity has been observed. Among the alkali metal doped CaO catalysts. Na-CaO (Na/Ca = 0.1. before calcination) catalyst (calcined at 750 degrees C), showed best performance (C(2+) selectivity of 68.8% with 24.7% methane conversion), whereas (lie poorest performance was shown by the Rb-Cao Catalyst in the OCM process.
Keywords: alkali metal doped CaO catalysts; basicity/base strength distribution; catalytic activity/selectivity; oxidative coupling of methane